(3TQM RHOI GdefGXQI aj GdBOGH ddhGYXs - (3eMehO Hf YHO Gddgs ((3eMeO Hf SdjeGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg bOQ GdhXGFa aj Gddjd hGdfgGQ hHYO ajbhd eMehO Hf YHO Gddg deG QCjJ QSGdI aj GdBOGH eTghQI Hjf GdYbdGA hGdENhGf aSQJgG CNPG ef cdGe GdaMhd s
(3BNQgG (B:s
(3hjMQQ aGdeQGO ef GdefY ggfG GdONd dcf dG hLg dbUQg efY Gddg YfG ehLHGJ GdCMRGf ef ZdHI GdNUe YdjfG aj HYV GdCRefIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3GdadSaI hGdefWbs